Play at child education: problematizing gender relations in school - Alcântara, Juliana Nascimento de; Dias, Alfrancio Ferreira; Givigi, Rosana Carla do Nascimento (Educação, 2019)
The purpose of this article is to discuss gender relations in early childhood education. This was a qualitative research, with observations made in classes with children between 5 and 6 years old in the public and collective environment of a Municipal School of Early Childhood Education of Aracaju, SE. The research took place between March and June 2018. The choices and ways in which the children put themselves in the games pointed to questions concerning educational practices in early childhood education, which establish the norms of the polarity of sexism in everyday school life. Finally, there is an urgent need to problematize gender issues from the earliest years of schooling. Implanted meanings in the collective unconscious need to be deconstructed and re-signified.